(untitled) (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. The research focus is on university athletes’ justification of cheating in sport. We hypothesised that moral disengagement would be more linked to more favourable evaluations of cheating in sports activities among athletes. Secondly it was hypothesised that justification of cheating in sport would be linked to gender and, accordingly, it would not be associated with experience in sport. Research aim was to reveal the dependence of the athletes’ assessment of cheating in their sports activities and moral disengagement in sport considering their personal factors Research methods. The sample included 338 (246 male and 92 female) athletes recruited from Lithuanian universities.The participants completed the Justification of Deception in Sport Scale (Sukys, Nickus, 2010) and the Moral Disengagement in Sport Scale-Short (MDSS-S; Boardley, Kavussanu, 2008). Research results. The regression analyses showed that gender of athletes was a significant predictor for justification of cheating in sport (β = 0.15, p < 0.01) as male student athletes more justified cheating in sport. Years of involvement in sport were not related with overall justification of cheating in sport. Moral disengagement in sport was a predictor for the overall justification of cheating in sport (β = 0.35, p < 0.001). Discussion and conclusions. Our study revealed the relationship between moral disengagement in sport and athletes’ justification of cheating in sport. Analysing different forms of cheating it was found that moral disengagement in sport was a stronger predictor for the justification of such deceptive actions that are linked to athletes’ manipulation of the rules of the sports and manipulation with the results of the sports contest. It was established that male student athletes more justified cheating in sport. Research results did not reveal relationship between overall justifications of cheating by years of involvement in sport. However, the analysis of the justification of different forms of cheating showed that students with less sports experience more justified deceptive actions linked to the manipulation with the results of the sports contest, and, on the contrary, less justified other forms of cheating in sport. Keywords: sport, justifcation of cheating in sport, moral disengagement in sport.